A Randomized Cohort Controlled Trial to Compare Intern Sign‐Out Training Interventions. Issue 12 (1st December 2017) - Lee, Soo‐Hoon; Terndrup, Christopher; Phan, Phillip H.; Zaeh, Sandra E.; Atsina, Kwame; Minkove, Nicole; Billioux, Alexander; Chatterjee, Souvik; Montague, Idoreyin; Clark, Bennett; Hughes, Andrew; Desai, Sanjay V.
Abstract : BACKGROUND: Although previous studies have investigated the efficacy of specific sign‐out protocols (such as the illness severity, patient summary, action list, situation awareness and contingency planning, and synthesis by reviewer [I‐PASS] bundle), the implementation of a bundle can be time consuming and costly. We compared 4 sign‐out training pedagogies on sign‐out quality. OBJECTIVE: To evaluate training interventions that best enhance multidimensional sign‐out quality measured by information exchange, task accountability, and personal responsibility. INTERVENTION: Four general internal medicine firms were randomly assigned into 1 of the following 4 training interventions: didactics (control), I‐PASS, policy mandate on task accountability, and Plan‐Do‐Study‐Act (PDSA). SETTING: First‐year interns at a large, Mid‐Atlantic internal medicine residency program. MEASUREMENTS: Eight trained observers examined 10 days each in the pre‐ and postintervention periods for each firm using a standardized sign‐out checklist. RESULTS: Pre‐ and postintervention differences showed significant improvements in the transfer of patient information, task accountability, and personal responsibility for the I‐PASS, policy mandate, and PDSA groups, respectively, in line with their respective training foci. Compared to the control, I‐PASS reported the best improvements in sign‐out quality, although there was room to improve in task accountability and responsibility. CONCLUSIONS: Different training emphases improved different dimensions of sign‐out quality. A combination of training pedagogies is likely to yield optimal results.